1996
DOI: 10.1002/(sici)1096-9071(199607)49:3<178::aid-jmv4>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of hepatitis C virus in Nigeria

Abstract: A pilot survey of hepatitis C virus (HCV) infection in Nigeria was carried out on healthy adult blood donors and children of preschool age. Sixteen of 200 (8%) donors were positive for antibodies using a second generation enzyme-linked immunosorbent assay (ELISA) but all of the children were negative. Supplementary testing of the ELISA-positives using a recombinant immunoblot assay (RIBA-2) confirmed the presence of antibody in four and two others were indeterminate. Four of the anti-HCV-positive sera and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…Genotype 5 has not been reported among co-infected patients before now. However, multiple genotypes including 1, 2 and 4 have been previously reported among the general population in Nigeria [42, 43], in addition to numerous reported sero-prevalence studies [44]. These reports show that even within regions in Nigeria, HCV genotypes are differentially distributed and this has serious implication for HCV vaccine development and management of infection in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype 5 has not been reported among co-infected patients before now. However, multiple genotypes including 1, 2 and 4 have been previously reported among the general population in Nigeria [42, 43], in addition to numerous reported sero-prevalence studies [44]. These reports show that even within regions in Nigeria, HCV genotypes are differentially distributed and this has serious implication for HCV vaccine development and management of infection in the country.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as in others ( 8 ), multiple sets of primers were needed to amplify these regions because different primer sets worked for different samples, which reflects the diversity of HCV. Our HCV Core/E1 tree showed 3 clusters.…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, perhaps true antibody-positive participants did not have positive RT-PCR results because they had cleared HCV viremia; however, in the industrialized world, most antibody-positive persons have persistent viremia. We did not confirm ELISA positivity with RIBA because, in Africa, few HCV ELISA-positive samples are confirmed by RIBA ( 3 , 8 ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 37% of HCV‐infected Lebanese patients with thalassaemia had genotype 4 13 . Several small studies from Africa suggest that HCV4 is the predominant genotype on that continent, 14–16 but a recent study from Cameroon in patients coinfected with HCV and HIV showed that HCV4 comprised only 16% of their patients, with genotype 1 being the most predominant genotype 16 …”
Section: Epidemiologymentioning
confidence: 99%